1995
DOI: 10.1104/pp.107.3.791
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nitrite Reductase Activity under CO2 Limitation in the Cyanobacterium Synechococcus sp. PCC7942

Abstract: During photoautotrophic growth under C0,-limited conditions, cells of Synechococcus sp. PCC7942 excreted into the medium about 30% of the nitrite produced by reduction of nitrate. No nitrite was excreted under C0,-sufficient conditions. After transfer of high-C0,-grown cells to C0,-limited conditions, nitrite reductase activity started to decline within 0.5 h and decreased to 50% of the initial leve1 in 3 h, whereas nitrate reductase activity was virtually unchanged. Nitrite started to accumulate i n the mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…When appropriate, kanamycin was added to the media at 25 g/ml. Expression of the nitrate assimilation genes was induced by transfer of ammonium-grown cells to the nitrate-or nitritecontaining medium as described previously (9).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…When appropriate, kanamycin was added to the media at 25 g/ml. Expression of the nitrate assimilation genes was induced by transfer of ammonium-grown cells to the nitrate-or nitritecontaining medium as described previously (9).…”
Section: Methodsmentioning
confidence: 99%
“…2, lanes 1 and 2). The size of the hybridization signal ranged from 0.25 to Ͼ7 kilobases representing rapid degradation of the nirA operon transcript (9). The NC2 and NC3 mutants also accumulated the transcripts hybridizing with the nrtD-specific probe when transferred to nitrate-containing medium (Fig.…”
Section: Construction Of Nrtc Deletion Mutants-inmentioning
confidence: 96%
See 2 more Smart Citations
“…The resulting ammonium is incorporated into carbon skeletons of the cell. It has been shown that nitrite, the product of nitrate reduction, was excreted into the medium under CO 2 -limited conditions (Azuara and Aparicio 1983;Krä-mer et al 1988;Suzuki et al 1995). Nitrite, the key factor concerned with the water quality in aquaculture, is quite toxic to zooplankton, shrimp, fish, etc.…”
Section: Introductionmentioning
confidence: 99%